Geminivirus-mediated delivery of florigen promotes determinate growth in aerial organs and uncouples flowering from photoperiod in cotton. - Roisin C McGarry (Public Library of Science (PLoS), 2012)
Background Plant architecture and the timing and distribution of reproductive structures are fundamental agronomic traits shaped by patterns of determinate and indeterminate growth. Florigen, encoded by FLOWERING LOCUS T (FT) in Arabidopsis and SINGLE FLOWER TRUSS (SFT) in tomato, acts as a general growth hormone, advancing determinate growth. Domestication of upland cotton (Gossypium hirsutum) converted it from a lanky photoperiodic perennial to a highly inbred, compact day-neutral plant that is managed as an annual row-crop. This dramatic change in plant architecture provides a unique opportunity to analyze the transition from perennial to annual growth. Methodology/principal findings To explore these architectural changes, we addressed the role of day-length upon flowering in an ancestral, perennial accession and in a domesticated variety of cotton. Using a disarmed Cotton leaf crumple virus (CLCrV) as a transient expression system, we delivered FT to both cotton accessions. Ectopic expression of FT in ancestral cotton mimicked the effects of day-length, promoting photoperiod-independent flowering, precocious determinate architecture, and lanceolate leaf shape. Domesticated cotton infected with FT demonstrated more synchronized fruiting and enhanced "annualization". Transient expression of FT also facilitated simple crosses between wild photoperiodic and domesticated day-neutral accessions, effectively demonstrating a mechanism to increase genetic diversity among cultivated lines of cotton. Virus was not detected in the F(1) progeny, indicating that crosses made by this approach do not harbor recombinant DNA molecules. Conclusions These findings extend our understanding of FT as a general growth hormone that regulates shoot architecture by advancing organ-specific and age-related determinate growth. Judicious manipulation of FT could benefit cotton architecture to improve crop management.